APPLICATION OF DE-ESCALATION NURSING INTERVENTIONS WITH EMOTIONAL EXPERIENCE WRITING IN CLIENTS WITH RISK OF VIOLENT BEHAVIOR - Wijiastuti, Galuh Tyas (JOURNAL EDUCATIONAL OF NURSING(JEN), 2024)
The risk of violent behavior in nursing diagnosis is usually arise because of aggressiveness which is often associated with people with schizophrenia. Affects and emotions in schizophrenic patients affect behaviors such as hand and body movements, facial expressions, and tone of voice that can be seen clearly when a person expresses and experiences feelings and emotions. This study aims to analyze the effectiveness of applying de-escalation with expressive writing exercises in reducing signs and symptoms of risk of violent behavior. The client is a 23-year-old woman with schizophrenia. The therapy given is generalist nurse intevention and by applying Emotional Experience Writing as a form of de- escalation. Emotional Experience Writing is part of expressive therapy that is used to help recovery and improve mental health. Emotional Experience Writing  is one of the intervention techniques developed from expressive writing therapy techniques used in counseling, psychotherapy, and rehabilitation. The procedure for implementing emotional experience writing is also based on expressive writing, which is oriented towards disclosing the emotional experiences experienced. The evaluation was carried out using an evaluation sheet for signs and symptoms of risk of violent behavior developed by the Department of Psychiatric Nursing, Faculty of Nursing, University of Indonesia. The results of this study indicate that the application of Emotional Experience Writing is effective in reducing the signs and symptoms in client with the risk of violent behavior. Emotional Experience Writing exercises are recommended to be an alternative de-escalation intervention, especially for clients with the risk of violent behavior.